2016
DOI: 10.1002/anie.201606102
|View full text |Cite
|
Sign up to set email alerts
|

Precise Formation of a Hollow Carbon Nitride Structure with a Janus Surface To Promote Water Splitting by Photoredox Catalysis

Abstract: The precise modification of redoxs pecies on the inner and outer surfaces of hollownanostructures is relevant in catalysis,surface science,and nanotechnology,but has proven difficult to achieve.H erein, we develop af acile approach to specifically fabricate Pt and Co 3 O 4 nanoparticles (NPs) onto the interior and exterior surface of hollowc arbon nitride spheres (HCNS), respectively,t op romote the surface redox functions of the polymer semiconductors.T he photocatalytic water splitting activities of HCNS wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
183
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 454 publications
(194 citation statements)
references
References 46 publications
1
183
0
1
Order By: Relevance
“…Moreover, double heterostructures based on C 3 N 4 have been proposed by Wang et al [108][109][110] to achieve the pure water splitting without sacrificial agents. Different from the previous discussed heterostructures, the double heterostructures are constructed by different co-catalysts on C 3 N 4 photocatalyst.…”
Section: −1mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, double heterostructures based on C 3 N 4 have been proposed by Wang et al [108][109][110] to achieve the pure water splitting without sacrificial agents. Different from the previous discussed heterostructures, the double heterostructures are constructed by different co-catalysts on C 3 N 4 photocatalyst.…”
Section: −1mentioning
confidence: 99%
“…For instance, modified separately with Pt and Co 3 O 4 NPs on both surfaces of C 3 N 4 , the photocatalytic full water splitting was achieved. [110] It indicates that the Janus structure can promote surface redox reactions by separating incompatible oxidation and reduction. It is anticipated that this methodology will realize the goal of designing full water splitting photocatalytic process with a well-designed H 2 /O 2 separation system.…”
Section: −1mentioning
confidence: 99%
“…[1] From both economic and environmental remediation viewpoints,i ti so fp articular interest to develop al owcost, stable,and environmentally benign system that can drive the overall water splitting reaction in an efficient manner. [2b] In recent years,s ubstantial efforts have been made to advance the properties of PCN,s uch as surface active-site regulation, [3] nanoarchitecture construction, [4] heterojunction design, [5] and band structure engineering. [2] The results have revealed that PCN in its pristine form only shows moderate activity because of its intrinsic properties,s uch as rapid charge-carrier recombination and moderate wateroxidation ability.…”
mentioning
confidence: 99%
“…[29] Recently,W ang and co-workers realized photocatalytic overall water splittingby using crystalline PTI modified with suitable co-catalysts.A sr evealed by DFT calculations,t he band gap of the PTI was straddled over the redox potential of water, which guaranteed that overall water splitting was thermodynamically feasible (Figure 8a). [29] Recently,W ang and co-workers realized photocatalytic overall water splittingby using crystalline PTI modified with suitable co-catalysts.A sr evealed by DFT calculations,t he band gap of the PTI was straddled over the redox potential of water, which guaranteed that overall water splitting was thermodynamically feasible (Figure 8a).…”
Section: Synthesis Characterization and Application Of Ccns In Watementioning
confidence: 99%